Updated review on Indian Ficus species - Bharat Singh; Ram A. Sharma (Arabian Journal of Chemistry, 2023)
As per Ayurvedic system of medicine, Indian Ficus (Fam. – Moraceae) plants are used in the treatment of various diseases. The plants are characterized by a specific class of closed inflorescence, named syconia, and are distributed in different states of India. Total 97 species of Ficus genus are naturalized in Indian states. Indian Ficus species possess anti-inflammatory, antimicrobial, antioxidant, antidiabetic, antiarthritic, antistress, anticancer, hepatoprotective, neuroprotective and wound healing properties. The phytochemical analysis reveals the presence of alkaloids, triterpenoids, flavonoids, furanocoumarins, and polyphenolic compounds in different species. Recently, bioavailability of Indian Ficus has been increased due to the presence of antioxidative agents. However, large number of reports have been published on phytochemistry and biological activities of 31 Indian Ficus species but, no reports are available in literature on 66 species. This review summarizes and describes the current knowledge of ethnomedicinal uses, phytochemistry, pharmacological activities, bioavailability, and pharmacokinetic profiles of 31 Indian Ficus species. Moreover, it includes clinical and toxicological studies with an aim to explore their potential in the pharmaceutical industries.